Alexithymic Trait, Painful Heat Stimulation, and Everyday Pain Experience - Pollatos, Olga; Dietel, Anja; Gündel, Harald; Duschek, Stefan (Frontiers in Psychiatry, 2015)
Background Alexithymia was found to be associated with a variety of somatic complaints, including somatoform pain symptoms. This study addressed the question of whether the different facets of alexithymia are related to responses in heat pain stimulation and its interrelations with levels of everyday pain as assessed by self-report. Methods In the study, sensitivity to heat pain was assessed in 50 healthy female participants. Alexithymia facets were assessed by the Toronto Alexithymia Scale. Pain threshold and tolerance were determined using a testing the limits procedure. Participants, furthermore, rated subjective intensities and unpleasantness of tonic heat stimuli (45.5–47.5°C) on visual analog scales and on a questionnaire. Possible confounding with temperature sensitivity and mood was controlled. Everyday pain was assessed by self-report addressing everyday pain frequency, intensity, and impairment experienced over the last 2 months. Results Main results were that the facets of alexithymia were differentially associated with pain perception. The affective scale “difficulties in describing feelings” was associated with hyposensitivity to pain as indicated by higher pain tolerance scores. Furthermore, everyday pain frequency was related to increased alexithymia values on the affective scale “difficulties in identifying feelings,” whereas higher values on the cognitive alexithymia scale “externally oriented thinking” were related to lower pain impairment and intensity. Conclusion We conclude that the different facets of alexithymia are related to alternations in pain processing. Further research on clinical samples is necessary to elucidate whether different aspects of alexithymia act as a vulnerability factor for the development of pain symptoms.